Pembatalan Hibah dalam Hukum Islam dan Perdata Indonesia dalam Teori Perikatan - Zulkarnain; Deni Rusli; Zakaria Syafe’i (Universitas Islam Tribakti Lirboyo Kediri, 2023)
This article discusses the cancellation of grants from the perspective of Islamic law and Indonesian civil law with an engagement theory approach. A grant is a legal transaction that involves a voluntary transfer of ownership, but there are situations where the grantor or grantee can cancel a grant. The purpose of this study is to analyze the views of Islamic law and Indonesian civil law regarding the cancellation of grants and explore the similarities and differences between the two legal systems in this context. Through an engagement theory approach, this article analyses the legal basis and requirements for grant cancellation in both legal systems. In Islamic law, grant annulment can be carried out based on Sharia principles that regulate the concept of hijab and qabul and the legal requirements of grants. On the other hand, Indonesian civil law regulates grant cancellation through the norms contained in the Civil Code and related laws and regulations. A comparative analysis is also conducted to identify similarities and differences in the views of the two legal systems regarding the reasons, procedures, and consequences of grant cancellation. In this context, this research provides an in-depth insight into the convergence or divergence between Islamic law and Indonesian civil law in addressing the issue of grant cancellation. The results of this research provide a deeper understanding of the relevant legal aspects in the context of grant cancellation in Islamic law and Indonesian civil law. By understanding their perspectives, parties involved in grant transactions can make more informed decisions and minimize the risk of future disputes. In addition, this article also contributes to the legal literature by exploring a comprehensive comparison between the two legal systems in this specific aspect.